2021
DOI: 10.1002/1878-0261.12922
|View full text |Cite
|
Sign up to set email alerts
|

Opposing prognostic relevance of junction plakoglobin in distinct prostate cancer patient subsets

Abstract: Both oncogenic and tumor suppressor functions have been described for junction plakoglobin (JUP), also known as c-catenin. To clarify the role of JUP in prostate cancer, JUP protein expression was immunohistochemically detected in a tissue microarray containing 11 267 individual prostatectomy specimens. Considering all patients, high JUP expression was associated with adverse tumor stage (P = 0.0002), high Gleason grade (P < 0.0001), and lymph node metastases (P = 0.011). These associations were driven mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Another difference was that SCC samples were enriched in cytoskeleton proteins, while BCC samples were not. Most of these cytoskeleton proteins have been previously described as present in the exosomes of diverse tumors (ExoCarta) ( 31 ) and have been related to poor prognoses such as LAD1, SFN, and JUP ( 32 , 33 , 34 , 35 ). Then, we propound that the differences between SCC and BCC-TIF composition could explain SCC aggressiveness and metastatic output.…”
Section: Discussionmentioning
confidence: 99%
“…Another difference was that SCC samples were enriched in cytoskeleton proteins, while BCC samples were not. Most of these cytoskeleton proteins have been previously described as present in the exosomes of diverse tumors (ExoCarta) ( 31 ) and have been related to poor prognoses such as LAD1, SFN, and JUP ( 32 , 33 , 34 , 35 ). Then, we propound that the differences between SCC and BCC-TIF composition could explain SCC aggressiveness and metastatic output.…”
Section: Discussionmentioning
confidence: 99%
“…Spethmann et al., demonstrated that the opposing biological roles of JUP were reflected by antagonistic prognostic effects in different molecular subtypes. High expression of JUP was associated with adverse tumor stage, high Gleason grade lymph node metastases in a subset of PCa patients without TMPRSS2:ERG fusion ( 46 ). Also, Overexpression of JUP was linked to strong androgen receptor expression, high cell proliferation, and PTEN and FOXP1 deletion ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…High expression of JUP was associated with adverse tumor stage, high Gleason grade lymph node metastases in a subset of PCa patients without TMPRSS2:ERG fusion ( 46 ). Also, Overexpression of JUP was linked to strong androgen receptor expression, high cell proliferation, and PTEN and FOXP1 deletion ( 46 ). On the other hand, it was found that SOX4 interacts with JUP in a Wnt-dependent manner in LNCaP cells and this complex may inhibit Wnt signaling ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, γ- and β-catenin were essential for maintaining leukemic stem cells in AML [ 72 ], while γ-catenin has also been found to be overexpressed in ovarian [ 73 ] and gastric cancer [ 74 ]. JUP expression in prostate cancer is controversial since changes depending on the stage [ 75 ]. In our study, JUP was found to be highly expressed in the SUP-B15 cell line and B-ALL individuals ( Figure 5 and Figure 6 A, respectively); moreover, its high expression yielded a significant correlation with worse overall survival in B-ALL ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%